Comparative analyses of SARS-CoV-2 binding (IgG, IgM, IgA) and neutralizing antibodies from human serum samples - Mazzini, Livia; Martinuzzi, Donata; Hyseni, Inesa; Benincasa, Linda; Molesti, Eleonora; Casa, Elisa; Lapini, Giulia; Piu, Pietro; Trombetta, Claudia Maria; Marchi, Serena; Razzano, Ilaria; Manenti, Alessandro; et al. (Journal of immunological methods, 2021)
A newly identified coronavirus, named SARS-CoV-2, emerged in December 2019 in Hubei Province, China, and quickly spread throughout the world; so far, it has caused more than 49.7 million cases of disease and 1,2 million deaths. The diagnosis of SARS-CoV-2 infection is currently based on the detection of viral RNA in nasopharyngeal swabs by means of molecular-based assays, such as real-time RT-PCR. Furthermore, serological assays detecting different classes of antibodies constitute an excellent surveillance strategy for gathering information on the humoral immune response to infection and the spread of the virus through the population. In addition, it can contribute to evaluate the immunogenicity of novel future vaccines and medicines for the treatment and prevention of COVID-19 disease. The aim of this study was to determine SARS-CoV-2-specific antibodies in human serum samples by means of different commercial and in-house ELISA kits, in order to evaluate and compare their results first with one another and then with those yielded by functional assays using wild-type virus. It is important to identify the level of SARS-CoV-2-specific IgM, IgG and IgA antibodies in order to predict human population immunity, possible cross-reactivity with other coronaviruses and to identify potentially infectious subjects. In addition, in a small sub-group of samples, a subtyping IgG ELISA has been performed. Our findings showed a notable statistical correlation between the neutralization titers and the IgG, IgM and IgA ELISA responses against the receptor-binding domain of the spike protein. Thus confirming that antibodies against this portion of the virus spike protein are highly neutralizing and that the ELISA Receptor-Binding Domain-based assay can be used as a valid surrogate for the neutralization assay in laboratories that do not have biosecurity level-3 facilities.